Employability skills of Malaysian community college student - Omar, Muhd Khaizer (2011)
Preparing the vocational education and employ ability skills of students is a vital in the higher education environment. The issue is how to induce a vocational experience to enhance students’ employability skills. If it is possible to give a realistic experience, the next challenge what is the best ways to measure if the students have actually developed their employ ability skills. This research is about to investigate the level of employ ability skills among the students. This study was conducted by administering a questionnaire to 329 students of various community colleges in Malaysia. The questionnaire contained employ-ability skills items from Secretary’s Commission on Achieving Necessary Skills (SCANS), in addition to questions reflecting age, gender, working experience, academic achievement and field of study. Descriptive and inferential statistics, such as the t-test, ANOVA, and Pearson Product-Moment Correlation, were used to analyze the data. The results revealed that the level of employ-ability skills of community college students was at a high level with (Mean = 3.63, S.D. = 0.47), comprises basic skills (Mean = 3.66, S.D. = 0.59), thinking skills (Mean = 3.61 , S.D. = 0.62), resources (Mean = 3.52, S.D. = 0.55),informational (Mean = 3.55, S.D. = 12:59), interpersonal skills (Mean = 3.72, S.D. = 0.71), system and technology skills (Mean = 3.53, S.D. = 0.62), and personal qualities (Mean = 3.86, S.D. = 0:59) respectively. The study also found that there was a positive relationship between age and employ ability skills. In addition,the findings also showed a significant difference between the employability skills of thinking skills [t (323) = 2:59, p <0.05] and the system and technology skills [t (323) = 1.98, p <0.05] based on gender, the where the males have better skills than females. In addition, there was no significant difference between students in terms of employability skills and possession or lack of working experiences. ANOVA analysis results showed that there were no significant differences between the mean values of employability skills and field of study and students’ academic achievement. The researcher believes that the decisions and requirements resulting from this study can serve to guide the selection,diagnosis, training and development of students at community colleges. Emphasis should be placed so that it needs to be realized in public institutions, technical and vocational education and industry involvement. Education should be able to expand the relationship with the industry by engaging curriculum that reflects the employ-ability skills.